(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The article analyzes the prosodic features of poetic texts included in the «modern poetic subcorpus» section of the National Corpus of the Kazakh Language. To date, poems and poetic works by Kazakh poets have been collected into the corpus database, marked with prosodic annotations, with each poet’s stylistic features identified and metatagged. Based on this poetic subcorpus, the rhythmic and intonational structures, syllabic-melodic systems, and phrase stress patterns of poems have been studied. The prosodic characteristics of poetic texts have been examined to determine their influence on poetic expressiveness. The aim of the “modern poetic subcorpus” is to present the works of Kazakh poets and highlight their prosodic features to a wide audience. In this context, the syntagms (bunaq) of the poems included in the subcorpus are marked with special symbols indicating melodic patterns and accompanied by the orphoepic (phonetic pronunciation) transcription of the text. The subject of the article is the poetry of the prominent Kazakh poet Tair Zharokov, whose works’ prosodic features within the poetic subcorpus are thoroughly analyzed. Special attention is given to the orphoepic transcription of his verses. The paper outlines the role and societal significance of this subcorpus in preserving the orphoepic norms of the Kazakh language. Alongside thematic content and the issues raised in the poetry, the importance of prosodic harmony in poetic structure is substantiated. This poetic subcorpus is positioned as a vital scientific and methodological tool that helps preserve the natural intonation and artistic structure of national poetry and enables the competent transmission of poetic texts to future generations. Keywords: prosody, suprasegmental, orthography, orthoepy, intonation, syntagma, meta-annotation.